Identification of amplified fragment length polymorphism markers associated with Karnal bunt (Neovossia indica) resistance in bread wheat - SINGH, SUKHWINDER; GREWAL, TEJINDER SINGH; SINGH, HARJIT; SODHI, MONIKA; DHALIWAL, H S (The Indian Journal of Agricultural Sciences, 2013)
Amplified fragment length polymorphism markers were used to study polymorphism and their association withKarnal bunt resistance genes in wheat (Triticum aestivum L. emend. Fiori & Paol.). Recombinant inbred lines developedfrom a cross of a Karnal bunt susceptible 'WL 711' and a Kamal-bunt resistant line 'HD 29' were tested forresistance to 2 Kamal bunt isolates through artificial inoculations. Study of parents and a set of recombinant inbredlines (selected on the basis of Karnal bunt reaction) for amplified fragment length polymorphism with 6 primer combinationswere analyzed and 336 loci scored. Of these, 77 were polymorphic between the parents. Three of the polymorphicmarkers were associated with Karnal bunt resistance genes.